Aprendizagem em movimento: uma plataforma para criação e uso de veículos de comunicação locativos - Pereira, Bernard Corrêa (2015)
Innovative Pedagogical Architectures require flexible computing resources in your configuration, to permit easy adaptation for use in educational activities planned by the educator. The “Learning in Movement” platform enables the modeling, execution and Monitoring of Communication Vehicles based in Location (VCLoc). A VCLoc is an interaction channel that considers the student’s physical location and allows you to record informations and maintain interpersonal relationships in field activities and extracurricular classes.